CONTROLLED-RELEASE FERTILIZER IN THE GROWTH OF Dalbergia nigra SEEDLINGS - Santos, Aline Ramalho dos; Gonçalves, Elzimar de Oliveira; Gibson, Elbya Leão; Araújo, Emanuel França; Caldeira, Marcos Vinicius Winckler (Floresta, 2020)
For the realization of forest restoration projects, it is essential to produce native seedlings in quantity, also necessary that they present greater vegetative vigor and good nutritional status. In this context, the objective of this work was to analyze the growth and nutrition of phosphorus of Dalbergia nigra seedlings from two sources cultivated with doses of controlled-release fertilizer (CRF). The experimental design was in randomized blocks, arranged in a factorial scheme 2 x 4, referring to lots of two seed sources of D. nigra (Viçosa, MG and Linhares, ES) and four doses of CRF (0, 2, 4 and 8 kg m-3), with four replications and 126 seedlings per plot. At 60, 90 and 120 days after sowing, the seedlings were collected to measure the variables related to growth and nutrition. D. nigra seedlings from Linhares (ES) show better growth and dry matter production. It is recommended to dose 7.46 kg m-3 of controlled-release fertilizer for seedlings from Linhares (ES) and the dose 5.99 kg m-3 for those coming from Viçosa (MG), aiming to maximize the growth of production of seedlings of D. nigra. Increasing doses of controlled-release fertilizer allow greater accumulation of P in shoot shoots of D. nigra.